Evaluation of Special Purpose Vehicle Organisation Skill Sets Taxonomy for Effective Public-Private Partnership Infrastructure Project Delivery - Gomez , Christy; Gambo, Muhammad (Penerbit Universiti Sains Malaysia, 2016)
The necessary skill sets that public-private partnership (PPP) stakeholders bring together are recognised as being paramount to the success of any PPP project. From preliminary research findings it is clear that there is a strong bias towards business-oriented skills rather than service-oriented skills by the special purpose vehicle (SPV) organisation. This paper examines the skills sets required to ensure the effective delivery and implementation of the private sector–led PPP project with respect to the SPV organisation in order to deliver value for money (VfM). A comprehensive literature review was conducted to establish the various skills needed by the SPV organisation for the successful delivery of PPP infrastructure projects to form the basis of the research questionnaire. Questionnaire survey data obtained from a purposive sample of 48 public and private PPP stakeholders in Peninsular Malaysia was analysed using SPSS v18 to establish the relative importance of the various skill sets. The findings indicate "legal and contracting knowledge" to be the most important and "conceptual skills" as the least important skill for the SPV organisation in PPP project implementation. The findings also indicated that there is a significant difference in the perception of public and private PPP stakeholders with respect to the importance of the "ability to clearly define technical and output specifications and standards for services to be procured", implying less importance given by the private sector with regard to this skill. Drawing on the understanding that skill sets are critical denominators of the organisational structure, this research is expected to influence the development of appropriate guidelines for skills prioritisation in the organisation of SPVs and the effective management of PPP concession projects.